Efeito da estimulação elétrica nervosa transcutânea associada à educação em dor em indivíduos com migrânea crônica: ensaio clínico randomizado - Dantas, Maria Ivone Oliveira (2025)
Introduction: Chronic migraine is defined as having headache attacks on 15 or more days per month, with at least 8 of them presenting typical migraine characteristics, for at least three consecutive months. Pharmacological treatment has limitations due to adverse effects and drug interactions, particularly in refractory cases. As an alternative, Transcutaneous Electrical Nerve Stimulation (TENS) has been explored for analgesia, while pain education aims to enhance the understanding of chronic pain and improve treatment adherence. Aim: To evaluate the effectiveness of TENS associated with pain education in the treatment of chronic migraine. Methods: Randomized clinical trial (No. 1.586.326) registered in the Brazilian Registry of Clinical Trials (RBR-6hmh7w). A total of 273 individuals were recruited, of whom 45 met the inclusion criteria and were randomly assigned to two groups: the experimental group (n=23) and the placebo group (n=22). The intervention group received TENS for 30 minutes, alternating between low (4 Hz) and high frequency (100 Hz) depending on the session (odd = low frequency; even = high frequency). The intensity was adjusted every five minutes, with a pulse duration of 100 μs. The placebo group received only 45 seconds of active stimulation with the same parameters. Both groups participated in 12 pain education sessions, conducted twice a week over six weeks. The analyzed outcomes included: (1) headache frequency, intensity, and duration, as well as somatosensory aspects of pain; (2) migraine-related disability and cervical function; and (3) headache impact and cognitiveemotional aspects. Results: (1) Both groups achieved an approximately 50% reduction in headache frequency, with no significant differences between them; (2) migraine-related disability decreased overtime in both groups, with no statistically significant differences; (3) TENS combined with pain education significantly reduced headache impact compared to the placebo group, with sustained benefits observed in the follow-up period. Conclusion: The TENS protocol with alternation between low and high frequency, when associated with pain education, showed relevant clinical effects in chronic migraine, especially in reducing the impact of headaches.